REPRESENTASI SOSIAL DAN POLITIK DI AMERIKA DALAM LIRIK LAGU AMERICAN IDIOT KARYA KELOMPOK MUSIK GREEN DAY - Diomena "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
American Idiot is a song with sosial-politic theme by American rock band, Green Day. This research aims to: First, find out the meaning of denotation on American Idiot song lyric. Second, find out the meaning of connotation on American Idiot song lyric. Third, find out the meaning of myth on American Idiot song lyric. Fourth, find out people’s viewpoint about social and politic in America on American Idiot song lyric.Method of this resesearch is qualitative research method with Roland Barthes’ semiotic approach. Data was collected through documentation (American Idiot song lyric), observation, and interview. Data analysis unit in this research consist of 16 lyrics line on the song American Idiot. In this research people’s viewpoint came from interview result with three informants who choose using purposive technique.Result of this research indicate that: First, according to denotation meaning represented appearing of a hysteria or over reaction from American society relate to information from media. Second, according to connotation meaning represented that informations from the media is a propaganda. Third, according to myth meaning represented that there is changing on social and politic of American society after the 9/11 tragedy. Next thing indicate that there is a discrimination to homesexual in America. Futhermore there is a sentiment beetwen people in North and South America relate to negative stereotype toward people in the South. Fourth, from people’s view point indicate that whole informant’s opinion support and suitable with result of this research.Key Words: Representation, Semiotic, Barthes’ Semiotic, American Idiot Song Lyric.